Kepo Digital sebagai Distorsi Curiosity: Sebuah Rekonstruksi Teologis Berdasarkan Hikmat Alkitabiah - Iman Kristina Halawa; Saut Maruli P. Panggabean (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
The phenomenon of digital kepo reflects a distortion of curiosity within contemporary social media culture. Curiosity, which fundamentally functions as a human capacity for seeking knowledge and meaning, is often transformed into the consumption of sensationalism, gossip, and social judgment. This study aims to reconstruct the phenomenon theologically through the concept of biblical wisdom (ḥokmâ) as a foundation for Christian digital ethics. The study employs a qualitative approach, using a normative-theological hermeneutical method, to analyze Proverbs 2:1–6, James 3:5–6, and Ephesians 4:29. The findings reveal that digital kepo constitutes a form of curiosity that has lost its moral and spiritual orientation because it is detached from divine wisdom. In contrast, biblical wisdom directs curiosity toward truth, love, and moral responsibility. This study proposes Christian Digital Wisdom as an ethical paradigm for reflective and spiritually formative digital communication practices.